Mechanical Feedback Control for Multicellular Tissue Size Maintenance: A Minireview - Hirashima, Tsuyoshi (Frontiers in Cell and Developmental Biology, 2022)
All living tissues and organs have their respective sizes, critical to various biological functions, such as development, growth, and homeostasis. As tissues and organs generally converge to a certain size, intrinsic regulatory mechanisms may be involved in the maintenance of size regulation. In recent years, important findings regarding size regulation have been obtained from diverse disciplines at the molecular and cellular levels. Here, I briefly review the size regulation of biological tissues from the perspective of control systems. This minireview focuses on how feedback systems engage in tissue size maintenance through the mechanical interactions of constituent cell collectives through intracellular signaling. I introduce a general framework of a feedback control system for tissue size regulation, followed by two examples: maintenance of epithelial tissue volume and epithelial tube diameter. The examples deliver the idea of how cellular mechano-response works for maintaining tissue size.